Interpretive activity in the judge’s professional occupation - Гураленко, Наталія Анатоліївна; Гураленко, Н. А.; Гураленко, Наталия Анатольевна; Huralenko, Nataliia A.; Волощук, Оксана Троянівна; Волощук, О. Т.; Волощук, Оксана Трояновна; Voloshchuk, Oksana T.; Сливка, Степан Степанович; Сливка, С. С.; Slyvka, Stepan S. (Editorial Primmate S. A. S., 2020)
The purpose of the article is a comprehensive analysis of the issue of the judge’s interpretive activity from the standpoint of the judge’s cognition in such a process of unchangeable dualism of the factual circumstances of the case and the norm of the law. To achieve this goal, such methods as dialectic, comparative, formal-logical, communicative and phenomenological was used. The article deals with the approach according to which the judge's interpretive activity during professional occupation is a necessary method of specifying the content of abstract, relatively defined legal norms; and these norms become applicable in solving certain debatable questions. It is concluded that the judge creates the search for the best solution of a particular legal position. Reconciling the uniqueness of the law case and the formality of the legislative provisions resolving case is impossible without interpretive activity. One of the peculiarities of the dynamics of the interpretive activity of the European Court of Human Rights is its intellectual and creative nature; mechanical transformation of the norms of law into individual acts and "stereotype" application of previous court decisions are not admissible. The judge's interpretive activity combines rational-technical and existential-semantic levels, which necessitates a high level of personal and professional maturity of the judge. The problem of interpretation is not only technical skills in legislative provisions; it covers an important "standpoint" of the reality based on the professional experience and legal consciousness.

Метою статті є комплексний аналіз проблеми інтерпретаційної активності судді з позиції пізнання суддею у такому процесі незмінного дуалізму фактичних обставин справи й норми закону. Для досягнення цієї мети використовувались такі методи, як діалектичний, порівняльний, формальнологічний, комунікативний та феноменологічний. У статті аргументується підхід, згідно з яким інтерпретаційна активність судді під час професійної діяльності є необхідним засобом, за допомогою якого зміст абстрактних, відносно визначених правових норм конкретизується, і вони стають застосовними при вирішенні окремих спірних ситуацій. Зроблено висновки про те, що суддя моделює пошук оптимального рішення щодо конкретної юридичної ситуації. Узгодження унікальності судової справи та формальності законодавчих приписів, які вирішують при вирішенні цієї справи неможливе без інтерпретаційної активності. Однією з особливостей динаміки інтерпретаційної активності Європейського суду з прав людини є його інтелектуальнотворчий характер; не допустимі механічна трансформація норм права в індивідуальні акти та «шаблонне» використання попередніх судових рішень. Інтерпретаційна активність судді поєднує в собі раціонально-технічний та екзистенційно-смисловий рівні, зумовлює необхідність високого рівня особистісної й професійної зрілості в судді. Проблема тлумачення не зводиться до суто технічної майстерності оперування законодавчими приписами, в ній важливим моментом є «кут зору» на дійсність, що виробляється на основі професійного досвіду й стійко закріплюється у правосвідомості.
Huralenko N. Interpretive activity in the judge's professional occupation / N. Huralenko, O. Voloshchuk, S. Slyvka // Amazonia Investiga. – Vol. 9. – Iss. 29. – Editorial Primmate S. A. S., 2020. – P. 427-435.
Keywords: decision of the ECHR; interpretation of law; legal argumentation; legal communication; legal consciousness; інтерпретація права; правова аргументація; правова комунікація; правова свідомість; рішення Європейського суду з прав людини; Research Subject Categories::LAW/JURISPRUDENCE